Safer pedestrian crossing facilities on low-speed roads: Comparison of innovative treatments. (February 2023) - Hussain, Qinaat; Alhajyaseen, Wael K.M.; Kharbeche, Mohamed; Almallah, Mustafa
Highlights: Different treatments were compared to improve pedestrian safety in residential areas. Physical narrowing treatment performed best in reducing conflicts. Physical narrowing treatment stimulated drivers' speed even in the absence of a pedestrian. Physical narrowing treatment is recommended to improve pedestrians' safety. Abstract: Despite the international efforts to improve pedestrian safety in different regions of the world, pedestrian fatalities still account for around one-third of annual road traffic deaths. Residential areas are commonly characterized by high pedestrian flows, making pedestrian safety a highpriority public health issue. Different types of treatments such as ITS-based, road markings, and physical treatments have been implemented to improve pedestrian safety, however, their efficiency varies between different locations worldwide. Therefore, this study aims to compare different innovative crosswalk treatments and to investigate their impacts on driving behavior in residential areas using a driving simulator. In our study, we juxtapose five different types of treatments with the untreated control condition. The treatments included two ITS-based solutions [LED pavement lights (ITS_LED) and Variable Message Sign (ITS_VMS)]; two different road markings [yellow zigzag marking (Marking_zigzag) and white road narrowing marking with the word SLOW written in the middle (Marking_narrowing)] and a physical road narrowing treatment (Physical_narrowing). Each of the tested conditions (control condition and treatment conditions) was tested with a Yield/Stop-controlled marked crosswalk located in a residential area with a posted speed limit of 50 km/h for two different situations. In the first situation, there was no pedestrian at the crosswalk (Situation PA), while in the second situation, a pedestrian was present at the crosswalk (Situation PP). Sixty-one volunteers possessing a valid Qatari driving license participated in the experiment. The study results showed that compared to the control condition, Physical_narrowing, ITS_VMS, and Marking_narrowing conditions helped to improve the yielding rates by 12.7 %. In terms of drivers' speed behavior, even though a pedestrian was not present at the crosswalk in Situation PA, physical_narrowing performed best by lowering the mean travel speed by around 10.1 km/h at the conflict location compared to the control location. Finally, the participants rated the physical_narrowing condition highest among the tested conditions. Based on the findings of the study, we conclude that the physical_narrowing treatment outperform other studied treatments since it significantly limits the freedom of drivers to maneuver, forcing them to slow down and give priority to crossing pedestrians.